Pro Paws Feeder For Cats And Dogs Using Arduino And Telegram Bot - Muhammad Amirul Iman, Hassan (2022)
This thesis aims to address the problem of pet owners facing difficulties in providing adequate food for their pets during extended periods of absence. The study proposes the development of a cost-effective solution, the Pro Paws Feeder (PPF) application, which functions similarly to expensive pet feeders available in the market. The PPF can be controlled remotely using a Telegram bot, with an Arduino Uno serving as the main controller connected to an online module for accessibility. The PPF is constructed using recyclable materials and incorporates a low-power motor to ensure a sustainable environment. The objectives of the research include studying existing pet feeders, designing, and developing the PPF to be affordable and efficient for pet owners, and evaluating its functionality. The scope encompasses users aged between 18-80 years with Telegram-enabled devices, primarily focusing on canine and feline owners. The development involves utilizing IoT technology and employing Arduino and C programming techniques. Upon completing this project, it shows that the PPF can fully functioned as intended. It feeds, read the status of the food, release food by its portion and many more without any problem at all. Telegram integration with PPF has been fully utilised and will be improved from time to time to properly function as we want it should be.